2020
DOI: 10.1111/bjet.13010
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of an adaptive learning system based on multimodal affect recognition for learners with intellectual disabilities

Abstract: Artificial intelligence tools for education (AIEd) have been used to automate the provision of learning support to mainstream learners. One of the most innovative approaches in this field is the use of data and machine learning for the detection of a student’s affective state, to move them out of negative states that inhibit learning, into positive states such as engagement. In spite of their obvious potential to provide the personalisation that would give extra support for learners with intellectual disabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In addition, the number of questions a student needs to answer to fully comprehend a given idea may be customized using these technological platforms. There is not a set of questions for each idea in advance [ 19 ]. To determine if a learner needs more practice with comparable problems or should go on to a more challenging level, the algorithm analyses their responses.…”
Section: Technological Structure Of Aimentioning
confidence: 99%
“…In addition, the number of questions a student needs to answer to fully comprehend a given idea may be customized using these technological platforms. There is not a set of questions for each idea in advance [ 19 ]. To determine if a learner needs more practice with comparable problems or should go on to a more challenging level, the algorithm analyses their responses.…”
Section: Technological Structure Of Aimentioning
confidence: 99%
“…The studies for designing teaching methods showed the roles and necessities of teaching procedures and interventions when applying ICT to education (Hwang & Yang, 2008;Martinez Borreguero et al, 2020;Repman, 1993;Woloshyn et al, 2017). For designing systems, their purposes were students' affect detection (Beege et al, 2018;Olugbade et al, 2020;Standen et al, 2020;Wu et al, 2014), reinforcement and feedback (Alepis et al, 2011;Rajendran et al, 2019;VanLehn et al, 2017), and both (Hwang & Yang, 2009). These studies found that environmental conditions for students' participation and flow were related to affective factors, so they attempted to collect and to utilize students' affective information.…”
Section: (Rq1-2) What Are the Research Purpose Trends?mentioning
confidence: 99%
“…First, in designing studies, outputs were systems and teaching methods. Systems were affective detectors (Richey et al, 2019;Standen et al, 2020;Wu et al, 2014), tutors for interaction between students and systems (VanLehn et al, 2017), and decision-making theory for affective judgment (Alepis et al, 2011). Teaching methods were instructional interventions that managed to change negative emotions in learning, such as frustration and boredom, into positive emotional responses and attitudes (Martinez Borreguero et al, 2020;Rajendran et al, 2019).…”
Section: (Rq2-3) What Are the Study Trends In Terms Of Affective Obje...mentioning
confidence: 99%
See 1 more Smart Citation
“…The meta-analysis by Wu, Huang & Hwang [13] did report on type of participant yet did not identify any with special needs. Given the potential of affect sensitive adaptive learning systems to provide personalised support, school-aged students with learning disabilities and autism were identified as a stakeholder group of the MaTHiSiS project [14] which aimed to use affective state and performance to drive the presentation of learning material in an adaptive learning system.…”
mentioning
confidence: 99%